Automatic home guarding system - Lim, Kheng Hee; Wahap, Ahmad Ridhwan (Penerbit UTHM, 2016)
An Automatic Home Guarding System is a system which helps to guard our house. The system consists of a main computer, a mobile robot with camera on it, and sensors to detect intrusion. Once the sensors detect an intrusion, the main computer will send an email to notify the user about the intrusion. Thus, even when the user is away from home, the user is able to get the notification as long as they stay online. After that, the user is able to watch the live video or see the images taken from his/her home where the intrusion is happening through internet. The videos and images can be saved in the computer for further use. By this the user can take further action on the incident.